THE MIDDLE OF NOWHERE: THE GAY RODEO’S ROLE IN FIGHTING THE SYMBOLIC ANNIHILATION OF QUEER RURALITY - (:unkn) unknown (My University, 2025)
ABSTRACT THE MIDDLE OF NOWHERE: THE GAY RODEO’S ROLE IN FIGHTING THE SYMBOLIC ANNIHILATION OF QUEER RURALITY by Eleanor Clement The University of Wisconsin-Milwaukee Under the Supervision of Professor Dr. Kristin Pitt This research explores how the community archives created by the International Gay Rodeo Association (IGRA) impact the symbolic annihilation of queer rurality in the archival record of gay liberation within the United States. Within academia the process of queer migration to urban areas and the process of assimilation to urban habitus has been more widely considered, largely ignoring the radical potential of queer rurality politically. This research was done by engaging directly with the material in the IGRA’s collection, considering not only the ways in which the records themselves may combat the imposed closet of metronormativity, but the impact of community centered archiving as a practice. The Reno Gay Rodeo and the surviving tradition of gay rodeo as a whole offers a distinctly rural queer lens by which metronormativity, within the collective memory of gay liberation, historically and contemporarily, may be challenged. Gay rodeo acts as an example of action that is not only locationally rural but is also symbolically rural and reflective of that lived experience. As the queer community faces continued challenges the need of a coalitionary politic that recognizes the rural as more than a place to escape is necessary for sustainable change. By deeply engaging with this material and utilizing it to construct countermemory to metronormativity these records can be used to inspire and guide current liberatory action.
Keywords: LGBTQ studies; Information science; Women's studies; Community Archiving; Gay Rodeo; Metronormativity; Rurality; Symbolic Annihilation